2021
DOI: 10.7759/cureus.16652
|View full text |Cite
|
Sign up to set email alerts
|

Goyal-Naqvi Syndrome (Concurrent Trisomy 10p and Terminal 14q Deletion): A Review of the Literature

Abstract: Goyal-Naqvi syndrome (GNS) is a newly documented clinical entity that comprises trisomy 10p and terminal 14q deletion, though trisomy 10p and terminal 14q deletion have been discovered as distinct conditions in 1974 and 1997, respectively. Nevertheless, to date, the total number of reported cases of each of these conditions is estimated to be in double digits. Both manifest as a constellation of features like craniofacial dysmorphism, hypotonia, intellectual impairment and global developmental delay. Character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…A subdural empyema develops as a result of septic thrombophlebitis of the mucosal sinus veins, which causes retrograde infection extension with bacterial drainage into the dural venous sinuses and cortical veins. Subdural empyema can also develop as a side effect of head trauma, from an infection of a subdural effusion, or from a direct infection of the subdural space occurring during a neurosurgical procedure like draining a subdural hematoma [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…A subdural empyema develops as a result of septic thrombophlebitis of the mucosal sinus veins, which causes retrograde infection extension with bacterial drainage into the dural venous sinuses and cortical veins. Subdural empyema can also develop as a side effect of head trauma, from an infection of a subdural effusion, or from a direct infection of the subdural space occurring during a neurosurgical procedure like draining a subdural hematoma [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…A thorough examination of the literature revealed that there are several research that show education had significant effect in improving the knowledge regarding bone density investigation and its importance and there by contributing in providing knowledge regarding the investigation and importance . This study represented a small effort to educate premenopausal women about low bone density research and its significance [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…'s genetic variations affect how it affects the brain. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The National Neuro AIDS Tissue Consortium is a Project that NINDS and NIMH are both fundings.…”
Section: Discussionmentioning
confidence: 99%